Transfer of clonal coffee seedlings from the conventional system to the modified hydroponic system - da Cunha, Samuel Henrique Braga; de Lima, Amador Eduardo; de Carvalho, Alex Mendonça [UNESP]; Guimarães, Rubens José; Teramoto, Érico Tadao [UNESP]; de Freitas, Ana Flávia (Revista Brasileira de Ciencias Agrarias, 2023)
Cloning plants by cuttings, mineral nutrition via modified hydroponics and the use of alternative substrates emerges as technological innovations for seedling production. The objective in this study was to evaluate the transfer of cuttings from the conventional system to the modified hydroponic system. The following variables were analyzed: seedling lenght; number of shoots; shoot lengnt; total leaf number; number of remaining leaves; leaf area; root area; stomatal conductance, density, and functionality; stomatal opening; root volume, area, length and diameter; leaf area ratio; specific leaf area and weight of specific leaf matter. For statistical analysis, a completely randomized design (CRD) with 5 treatments, six replications and ten plants per plot was used. From the results obtained, it is possible to conclude that: the rooting of Coffea arabica cuttings is not necessary in a conventional system, and it can be performed directly in a modified hydroponic system; an adaptation in the proposed modified hydroponics system with nebulization in the environment is necessary for rooting, for the obtention of a higher quality seedling.
Keywords: cloning; coffee tree; greenhouse; vermiculite